ВПЛИВ РОЗПОДІЛУ ВТРАТ ЕНЕРГІЇ В ЕЛЕМЕНТАХ АВТОТРАНСФОРМАТОРА ТРАНСФОРМАТОРНО-КЛЮЧОВОЇ ВИКОНАВЧОЇ СТРУКТУРИ СТАБІЛІЗАТОРА НАПРУГИ НА ЕФЕКТИВНІСТЬ ВИКОРИСТАННЯ ЙОГО ВСТАНОВЛЕНОЇ ПОТУЖНОСТІ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки Національної академії наук України, 2019)
The mass-wide characteristics of the transformer-and-switches executive structure (TSES) of the AC voltage stabilizer are determined exclusively by the efficiency of using the installed power of the selected autotransformer (AT). The increase of this parameter, subject to the limitation of the maximum temperature of the elements of AT, which depends on the total energy losses in them, is associated with a change in the magnitude and ratio of losses in the core of the magnetic core and sections of the AT winding. The degree of influence of the transition to electrotechnical steel for a magnetic core with less losses and/or an increase in the calculated value of worker induction is studied. The thermal state of the AT elements for the four variants of the ratio of losses in them is illustrated on the 3D models of the object. References 11, figures 2, table 1.